UPAYA HUKUM PENINJAUAN KEMBALI PERKARA KEPAILITAN BERDASAR PUTUSAN MAJELIS HAKIM TENTANG PERMOHONAN PKPU (TINJAUAN YURIDIS PUTUSAN HAKIM MA NO. 134-PK/Pdt.Sus Pailit/2016) - Farida, Farida Sofa (Faculty of Law Universitas Lancang Kuning, 2023)
As for the subject of the formulation of the problem in this journal article is regarding whether the legal remedy for review of the decision on the PKPU application in decision N0. 13/PKPU/2015/PN Niaga Sby is in accordance with the Bankruptcy Law and PKPU. The method used is normative juridical. Based on the results of the research, it was found that the judicial review was not in accordance with the Bankruptcy and PKPU Laws because it had exceeded the specified time limit, namely 180 days after the date of the decision being filed for a permanent legal review. This means that the application for review submitted is around 184 days since it has permanent legal force.